Bronia Baum, „Dziennik z lat 1912–1921” - Lisek, Joanna (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2019)
Bronia (Brejndl) Baum (1896–1947) was an orthodox writer, activist and publicist. She was born in a Hasidic family in Tomaszów Mazowiecki. She published poems and articles in Yiddish in “Der Jud”, “Dos Jidisze Togblat”, “Bejs Jakow” and in Hebrew in “Bat Izrael”, “Baderech”. In the family archive among the manuscripts of Bronia Baum from 1912–1921, a diary written in Russian has been preserved. Considering the content and form of records, it can be most accurately described as an intimate diary. The notes of Bronia Baum are a valuable source for research in the field of local Jewish history, especially during the First World War, but also for issues related to Jewish orthodoxy, Zionism and religious feminism.